A time-series analysis of the momentum of the athlete-discus system in the discus throw - Kato, T.; Mizushima, J.; Maeda, K. (Journal of Sports Sciences, 2026)
Release velocity is one of the most critical factors determining the discus throw distance. The purpose of this study was to clarify the role of athlete-discus system momentum - the primary source of release velocity - by analysing its time-series data. Twenty-six discus throwers were recorded during official competitions, and the 3D-DLT method was applied to calculate the system`s centre of mass (COM), velocity (vSystem), linear momentum (pSystem), angular momentum (LSystem) and normalised angular momentum (bSystem) around the system`s COM. SPM-1D regression analysis was used to examine the relationships between these momentum-related variables and release velocity. Two main findings emerged from the results: (1) only LSystem around the vertical axis and the resultant LSystem showed significant positive correlations with release velocity and (2) LSystem, bSystem, vSystem and pSystem all exhibited significant positive correlations with the resultant LSystem at the moment of discus release. Although LSystem was correlated with the release velocity, it was revealed that the linear variables affected the resultant LSystem and indirectly affected the gain in release velocity. The study highlighted the importance of linear motion, which had not been previously emphasised in terms of gaining release velocity in discus throw.